A eficiência dos meios executivos na tutela processual das obrigações pecuniárias no Código de Processo Civil de 2015 - Rosado, Marcelo da Rocha (2018)
The purpose of this dissertation is to investigate how the efficiency of executive means can be achieved for the protection of pecuniary obligations in the Brazilian procedural system, based on dogmatic proposals aimed at the fulfillment of the general clause of effectiveness of article 139, IV, of the Civil Procedure Code of 2015. The study presents proposals for understanding the typical and atypical model of executive means in the procedural system, taking as a premise the need to shape a system that is not only complete but also efficient for the protection of these obligations, based on the necessary interaction of the general clause with other legal norms of the system, especially those that convey the principles of efficiency and the lowest onerosity. It is understood that the model devised by the CPC/15 for the protection of credit is a new model, which also demands new ways of thinking, overcoming ideas sedimented under another context, which no longer meet the real needs of the executive protection of pecuniary obligations. For the development of the theme, doctrinal premises are reaffirmed on the understanding of the execution process based in the identification of executive protection as a fundamental right, which is a crucial point of support for the reflections on how executive acts should be applied and how the interests in tension in the execution must be weighed. It is exposed how should be the judicial action to build the efficient legal solution without sacrificing legal security, considering the inherent risk of a procedural system that contemplate the atypicity of executive means. It is also possible to identify, from a theoretical framework on the techniques that the legal system can use to achieve its results, which are the measures that can be adopted for the implementation of the executive judicial protection, followed by proposals for implementation efficient analysis of the atypical executive means, with the analysis of the controversial doctrinal positions on the execution of the executive general clause in the execution of pecuniary obligations. Finally, a critical analysis of judicial decisions on the subject is made, and the final conclusions of the research are presented.